Desain Power Amplifier Frekuensi 135 Mhz Untuk Transmiter VHF Dittel Portable - Firmansyah, Teguh; Kuswara, Gatot; Prasetyo, Windu (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2016)
Power amplifier (PA) is the final component in the DITTEL Portable VHF transmitter with fucuntion to amplify the signal that is sent from the source. In this paper, the power amplifier is made to work at a frequency of 135 Mhz. PA proposed using Type Mosfet transistors MRF 136 with power supply V = 30 V, VDD = 28 V and ID = 1.2 A in order to obtain the gain and output power are great. To boost the coverage area of communication at the time of check calibration flight. Design PA using L-Network and phi- Matching is used as an input matching circuit and output matching. Type bias transistor used is a power-divider because it has the sensitivity of the lowest changes to temperature changes. The results of the simulations and calculations have been carried out, the result obtained from the specification of power amplifier : stability values> 1, the gain (S21) = 20 dB, output return loss (S11) = -33.89 dB. With a power output as expected at 10 watts or 40 dBm at frequency 135 MHz.